2018
DOI: 10.2319/022118-139.1
|View full text |Cite
|
Sign up to set email alerts
|

Orthodontic appliances did not increase risk of dental caries and periodontal disease under preventive protocol

Abstract: Objectives: To assess periodontal parameters and microbial species levels after orthodontic appliance placement in patients who received oral hygiene instructions and who were monitored and motivated throughout the study. Materials and Methods: The Periodontal Index was recorded and saliva collection was performed before (T0) and 30 (T1), 60 (T2), and 90 (T3) days after orthodontic appliance placement in 15 patients (mean age 17.53 6 8.0 years). Analysis was carried out using checkerboard DNA-DNA hybridization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
1
11

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 35 publications
0
26
1
11
Order By: Relevance
“…In another review article, the authors reported orthodontic treatment to be a risk factor for dental caries, especially in younger patients 3 . However, a recent study 16 reported that orthodontic treatment is not a risk factor for dental caries if an appropriate oral-care protocol is implemented. However, a recent study 16 reported that orthodontic treatment is not a risk factor for dental caries if an appropriate oral-care protocol is implemented.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In another review article, the authors reported orthodontic treatment to be a risk factor for dental caries, especially in younger patients 3 . However, a recent study 16 reported that orthodontic treatment is not a risk factor for dental caries if an appropriate oral-care protocol is implemented. However, a recent study 16 reported that orthodontic treatment is not a risk factor for dental caries if an appropriate oral-care protocol is implemented.…”
Section: Introductionmentioning
confidence: 99%
“…They emphasised that clinicians should educate patients about prevention of dental caries before orthodontic treatment is initiated and should not recommend orthodontic treatment to patients who are not motivated to perform good dental hygiene. Malocclusion in itself may also be a risk factor for dental caries 16 , and it has been reported that patients who are receiving orthodontic treatment have an improved ability to manage their oral hygiene 17 . Moreover, orthodontic treatment is indispensable in resolving malocclusion, which may be mild (such as crowding) or severe (such as impaction or abnormal tooth eruption), causing serious oral dysfunction 1 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A preventive protocol, based on motivation and instruction on the correct oral hygiene maneuvers before and during orthodontic treatment, decrease the risk of dental caries and periodontal disease in patients with fixed corrective devices This statement was demonstrated through a study that assessed periodontal parameters and levels of microbial species after placement of fixed orthodontic appliances in patients who received oral hygiene instructions and were monitored throughout the duration of treatment.The periodontal index registered initially did not change to the 90-day control, the total amount of the purple and red complexes and the candida species decreased at T2 (60 days from the placement of the orthodontic appliance), the green, yellow, and orange complex showed a significant decrease at T3 (90 days from the placement of the orthodontic appliance). [13]. Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The Streptococcus spp. decreased levels from T2 onwards [13,14]. In light of the above, the early diagnosis of supernumerary teeth is important for an accurate treatment plan.…”
Section: Discussionmentioning
confidence: 99%